Public transport accessibility and efficiency as determinants of urban image: A comparative study of Japanese and Nigerian Cities - Sani Inuwa Sani; Raldi Hendro Seputro Koestoer; Abubakar Hassan Adam; Aliyu Aminu Umar; Hafsat Sani Yau; Mubarak Ahmad Hassan (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Public transport is a defining feature of urban identity and city authenticity, shaping how cities function and are perceived globally. This study compares the accessibility and efficiency of public transportation in selected Japanese and Nigerian cities from 2021 to 2025 to understand how mobility systems contribute to city branding and livability. Japan’s transport network is celebrated for punctuality, integration, and environmental awareness, while Nigeria’s is constrained by congestion, poor infrastructure, and heavy reliance on informal systems. Examining these differences reveals how transport systems influence both functional mobility and the symbolic authenticity of urban spaces. Methods: A systematic review and bibliometric analysis were conducted following the PRISMA 2020 guidelines. Literature was retrieved from the Scopus database using structured keywords related to urban transport, accessibility, and efficiency. A total of 1,088 records were screened, with 32 peer-reviewed studies meeting inclusion criteria. Data were analyzed using R (v4.4.2) and the Bibliometrix package in RStudio to produce thematic maps, co-occurrence networks, and trend analyses that reveal major research themes and geographic emphases. Findings: Results show that “urban transportation,” “accessibility,” and “sustainability” dominate research discourse. Japanese studies emphasize innovation, multimodal integration, and environmental efficiency, strengthening city authenticity and competitiveness. Nigerian studies highlight infrastructure gaps, congestion, and socioeconomic inequality in access, though emerging reforms and public–private initiatives show gradual progress. Conclusion: Efficient and accessible transport systems enhance city authenticity and livability while reinforcing urban branding. Lessons from Japan’s integrated mobility governance can inform sustainable transport strategies in developing cities like Nigeria. Novelty/Originality of this article: This study is the first comparative bibliometric review linking public transport accessibility and efficiency to city branding and authenticity, integrating systematic review methods with bibliometric visualization to advance the discourse on sustainable urban identity.